A comparison of the coping methods with stress of mothers of children with mental-retardation, Cerebral-Palsy and normal children - S. Aghababaei; N. Esteki Azad; A. Abedi (پژوهش‌های علوم شناختی و رفتاری, 2013)
The aim of this research was to compare the stress coping methods of mothers of children with mental- retardation, cerebral-palsy and normal children. The design of this research was ex- post- facto. Therefore, ninety mothers of children with mental-retardation, cerebral- palsy and normal children were randomly selected. The instrument was Roger’s Stress Coping Methods Scale. The results of analysis of variance showed that there was a significant difference between coping methods with stress of mothers of children with mental-retardation, cerebral-palsy and normal children (P<0.001). The findings indicated that mothers of children with mental retardation used more negative coping methods.